Impacto das doenças respiratórias em bezerras leiteiras: revisão bibliográfica - de Andrade, Maria Paula Caetano (2021)
This review covered scientific articles on some respiratory diseases that affect dairy calves. Diseases related to the systems of raising calves until weaning, during which animals are more susceptible to different diseases. To this end, information was used from various sources, including research institutions, specialized websites, national and international dissemination magazines, technical bulletins, technical circulars, articles published in national and international journals and books. In diseases of the respiratory tract, pneumonia is one of the main causes of economic losses within the calf rearing, reducing the performance of these animals and consequently leading to a delay in the beginning of productive life. Among the main agents that cause this pathology are viruses such as respiratory syncytial virus and herpes virus, acting in isolation or as primary agents for the entry of secondary infections, often of bacterial origin. The main bacteria that affect the respiratory tract are Pasteurella multocida, Mannheimia haemolytica, Haemophilus somnus and Mycoplasma bovis, causing the disease whenever the animal is subjected to stress conditions, causing the immunity to fall. In this context, lose the habit of medicating, and start to prevent it, using management methods to improve the performance and well-being of both animals and people involved in dairy farming